The future of conventional newspaper in the era of post digital revolution: an escalation of reading preference. - Abdul Rahman, Saiful Nujaimi; Mahayuddin, Muhammad Mahfuz Fahmi; Omar, Siti Zobidah; AlSagoff, Syed Agil (2008)

(untitled)
Compact newspaper as the latest public reading preference is no longer a mere speculation. This new hybrid of journalistic medium has become the latest reading trend in today's era of post digital revolution. This new journalistic horizon, nevertheless, must be embraced by the media organizations with precise comprehension of its spiritual and physical demands and needs. Concisely, today's public reading preference has skewed to a fresher and simpler medium of news presentation – the compact newspaper. This phenomenon has made many media organizations paused to restructure their operations to cater the demand and needs of the new horizon of communication revolution. Hence, this paper began with a few queries – among others are in finding out the areas of reformation that had been accomplished by the Malaysian media organizations in fulfilling the increasing demands of the public on compact newspapers, and in determining the key factors that triggered the change of reading preference on newspapers among the Malaysian. Throughout this paper, two different research findings (of two different years) on compact newspapers will be comparatively analyzed and presented. Both of those findings may somehow alter our perception on how different is the contemporary public gratify their contemporary media. These two combined researches were expected to instil a better understanding on the possibilities of future threats and obstacles that may befall unto any conventional newspapers. In short, this research paper aspires to generate better understanding on compact newspapers' reading preference – not only among the Malaysian public, rather in ensuring the future significance and relevance of any conventional newspapers of any country in this millennium.